2013
DOI: 10.1089/hum.2012.168
|View full text |Cite
|
Sign up to set email alerts
|

The Nontoxic Cell Cycle Modulator Indirubin Augments Transduction of Adeno-Associated Viral Vectors and Zinc-Finger Nuclease-Mediated Gene Targeting

Abstract: Parameters that regulate or affect the cell cycle or the DNA repair choice between non-homologous end-joining and homology-directed repair (HDR) are excellent targets to enhance therapeutic gene targeting. Here, we have evaluated the impact of five cell-cycle modulating drugs on targeted genome engineering mediated by DNA double-strand break (DSB)-inducing nucleases, such as zinc-finger nucleases (ZFNs). For a side-by-side comparison, we have established four reporter cell lines by integrating a mutated EGFP g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 59 publications
0
19
1
1
Order By: Relevance
“…It has been shown that small molecule compounds can effectively activate or block certain DNA repair pathways (Hollick et al, 2003; Rahman et al, 2013; Srivastava et al, 2012). However, it remains unclear whether small molecules could be used to modulate CRISPRinduced genome editing and DNA repair via the HDR pathway.…”
mentioning
confidence: 99%
“…It has been shown that small molecule compounds can effectively activate or block certain DNA repair pathways (Hollick et al, 2003; Rahman et al, 2013; Srivastava et al, 2012). However, it remains unclear whether small molecules could be used to modulate CRISPRinduced genome editing and DNA repair via the HDR pathway.…”
mentioning
confidence: 99%
“…In what the latter genome editing approaches are concerned, these experiments involved the targeting of both reporter and endogenous loci after the delivery of ZFNs and gene correcting templates into a diverse panel of human cell types. These different cell types included, U2OS osteosarcoma cells, 47 , 48 HEK 293 cells, 46 HeLa cervix carcinoma cells, 48 HT-1080 fibrosarcoma cells, 48 and bona fide human embryonic stem cells (ESCs) as well as iPSCs. 49 Noticeably, due to the very diverse range of tools, experimental models and conditions, the gene-targeting frequencies in both absolute and relative terms ( i.e.…”
Section: Viral Vectors As Gene-editing Toolsmentioning
confidence: 99%
“…Single-strand DNA vector genomes are uncoated within the nucleus and form discrete foci whose abundance directly correlates to the transduction efficiency (128, 147). The generation of a DNA molecule competent for transcription is dependent upon the genome concentration within the nucleus.…”
Section: Adeno-associated Virus Vector Transduction and Optimizationmentioning
confidence: 99%
“…In particular, the role of intact cell cycle checkpoints, and the growth phase in general, also appear to affect transduction and furthermore, confound the direct implication of cell cycle regulators, such as ATM and p53, as controllers of AAV vector transduction. As mentioned above, several genotoxic stresses that also arrest the cell cycle result in increased transduction (9, 147). The mechanism of this enhancement is not completely understood but could be explained by the sequestration of repair factors that are reported to inhibit rAAV transduction away from the AAV genome (such as the MRN complex).…”
Section: Adeno-associated Virus Vector Transduction and Optimizationmentioning
confidence: 99%